A Study of Presupposition and Conversational Implicatures in the Comic Strip of “The Diary of a Wimpy Kid” - Helena Verusha Ali; Dini Hidayati; Yanuarius Yanu Dharmawan (Universitas Cokroaminoto Palopo, 2023)
This study aims at exploring the application of presupposition and conversational implicature in communication within comic strips from pragmatics field of study as proposed by Yule, (2006). The research design of this study is a qualitative design. The data were utterances and sentences in